Wildcats - Hawn, Goldie; Keach, James; Kurtz, Swoosie; Sacks, Ezra.; Sylbert, Anthea; Ritchie, Michael, 1938-2001.; Warner Home Video (Firm); Warner Bros. Pictures (1969- ) (Burbank, CA : Warner Home Video, 2006)
Molly McGrath becomes coach of the football team at Central High School, and turns the team into a winning team.
Originally produced as a motion picture in 1986.
Special features: training montage music video; cast/crew filmographies; theatrical trailer.
Director of photography, Donald E. Thorin ; edited by Richard A. Harris ; music by Hawk Wolinski & James Newton Howard.
Goldie Hawn, James Keach, Swoosie Kurtz.
DVD, region 1, widescreen, Dolby digital surround stereo.
English or French language tracks; optional subtitles in English, French, Spanish, Portuguese, Japanese, Chinese, Thai. Closed-captioned.
Keywords: School sports -- Drama; Football -- Drama; Football -- Coaching -- Drama; Feature films (V-Z).; DVD-Video discs; Comedy films; Drama; Feature films; Fiction films; Video recordings for the hearing impaired; Comedy -- Feature